2008
DOI: 10.1209/0295-5075/84/57001
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity in the half-filled Holstein-Hubbard model

Abstract: Abstract. -We re-examine the Peierls insulator to Mott insulator transition scenario in the one-dimensional Holstein-Hubbard model where, at half-filling, electron-phonon and electron-electron interactions compete for establishing charge-and spin-density-wave states, respectively. By means of large-scale density-matrix renormalization group calculations we determine the spin, single-particle and two-particle excitation gaps and prove-in the course of a careful finite-size scaling analysis-recent claims for an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
125
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 31 publications
10
125
1
Order By: Relevance
“…The U -λ phase diagram determined in our study is qualitatively similar to that found by low temperature numerical approaches, with the U eff =0 line dividing the regions of dominant spin and charge order parameters. We found evidence for an intermediate metallic phase in two dimensions, similar to previous 1-d results.. [14][15][16][17] The size of the intermediate metallic region shrinks as the interaction strengths grow, which is consistent with Refs. 15-17 where the metallic phase is found to terminate at strong couplings.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The U -λ phase diagram determined in our study is qualitatively similar to that found by low temperature numerical approaches, with the U eff =0 line dividing the regions of dominant spin and charge order parameters. We found evidence for an intermediate metallic phase in two dimensions, similar to previous 1-d results.. [14][15][16][17] The size of the intermediate metallic region shrinks as the interaction strengths grow, which is consistent with Refs. 15-17 where the metallic phase is found to terminate at strong couplings.…”
supporting
confidence: 92%
“…In one dimension, the HH phase diagram has been established via several numerical approaches, with an intermediate metallic state between the AFM and CDW phases. [14][15][16][17][18] The size of the metallic region grows with increasing phonon frequency. [15][16][17] A similar competition between AFM and CDW orders and phase diagram have been mapped out in infinite dimensions with DMFT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spin gap is a result of backscattering. Signatures of this LutherEmery phase have also been observed in the Holstein-Hubbard model with comparable electron-phonon and electron-electron interactions [38,18,19,22,23]. Our results presented below suggest that in contrast to half filling, we can observe dominant pairing correlations for high phonon frequencies at a commensurate density; dominant pairing for incommensurate filling has been reported before [39].…”
Section: Model and Methodssupporting
confidence: 81%
“…We usually notice the ratio between U and t (U/t), since SDW order depends on U/t. 29,30 The increasing of positive strains leads to the reducing of the neighbor hopping t, but on-site U just changes little, which indicates positive strains will increase the value of U/t. Accordingly, positive strains can increase the SDW magnetic moments and band gaps, while electrons become more and more localized.…”
Section: 52k B T S Dwmentioning
confidence: 99%